2017
DOI: 10.1007/s10877-017-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy monitoring during immediate transition after birth: time to obtain cerebral tissue oxygenation

Abstract: Feasibility of cerebral tissue oxygenation measurements immediately after birth has been published starting with first values 2 min after birth. Aim of this study was to evaluate, the time periods from birth and from arrival at the resuscitation table to obtain the first cerebral tissue oxygenation values with two different near infrared spectroscopy (NIRS) devices. The present study is an analysis of exploratory parameters of two prospective observational studies. Cerebral tissue oxygen saturation was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Cerebral StO 2 by frontoparietal TRS sensor followed the rise in SpO 2 , similarly to previous observations performed on the same population using other NIRS techniques 23–28 30 31. Indeed, StO 2 values derived from TRS seem grossly comparable with values obtained by NIRO300,24–26 FORE-SIGHT cerebral oximeter,27 IMUC700028 (although some of these studies censored data points where StO 2 exceeded SpO 2 , which we did not do) but lower than values measured by INVOS5100 with neonatal sensors 23 25 30 31. This observation is consistent with previous studies reporting significantly higher regional StO 2 values when using paediatric and neonatal sensors compared with the INVOS5100 adult sensors 33 34…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cerebral StO 2 by frontoparietal TRS sensor followed the rise in SpO 2 , similarly to previous observations performed on the same population using other NIRS techniques 23–28 30 31. Indeed, StO 2 values derived from TRS seem grossly comparable with values obtained by NIRO300,24–26 FORE-SIGHT cerebral oximeter,27 IMUC700028 (although some of these studies censored data points where StO 2 exceeded SpO 2 , which we did not do) but lower than values measured by INVOS5100 with neonatal sensors 23 25 30 31. This observation is consistent with previous studies reporting significantly higher regional StO 2 values when using paediatric and neonatal sensors compared with the INVOS5100 adult sensors 33 34…”
Section: Discussionsupporting
confidence: 89%
“…These results are similar to those reported by previous studies during transition: Urlesberger et al 23 measured 50% of infants by 3 min using INVOS5100 and Baik et al 24 measured 79% of newborns by 3 min with NIRO. Shorter starting time are reported by Ziehenberger et al ,25 with NIRO or INVOS5100C (mean: 95 s and 93 s, respectively), Fauchere et al 26 with NIRO (median: 2 min; range: 1–4 min), Almaazmi et al 27 with FORESIGHT (median time to signal: 63 s; IQR: 38–88 s) and Isobe et al 28with IMUC7000 (measurement begun at 1–2.5 min).…”
Section: Discussionmentioning
confidence: 72%
“…Near-infrared light is safe and penetrates deeply in the body, and NIRS has recently been applied for functional evaluation of cerebral circulation and oxygenation state in neonates [1]. Several studies have reported on the measurement of cerebral oxygenation via the tissue oxygenation index or regional saturation of oxygen (rSO 2 ) in neonates during the immediate transition after birth using NIRS [2][3][4][5][6][7][8]. Furthermore, NIRS can measure changes in venous Hb concentration (tHb) and cerebral blood volume (CBV), with some work showing a decrease in CBV in term neonates in the first 15 min after birth [9].…”
Section: Introductionmentioning
confidence: 99%
“…The reference value for SpO 2 at 5 minutes after cesarean birth was reportedly 85% (60%-94%) [20]. Similar devices using NIRS have also been used for measuring neonatal oxygenation immediately after birth; however, not all the values obtained by such devices have been reliable [21][22][23]. Median values for the cerebral tissue oxygen saturation index (NIRO-200NX, Hamamatsu Photonics K.K., Hamamatsu, Japan) and for the regional cerebral tissue oxygen saturation (INVOS 5100, Somanetics Corp, Troy, MI) were 65.6% and 66.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%